PENGEMBANGAN BAHAN AJAR BERMUATAN BUDAYA BATAK BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATERI PECAHAN KELAS IV SDN 067257 KEC. MEDAN AMPLAS - Nabila, Talitha; Darwis, Umar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop mathematics teaching materials based on Problem Based Learning (PBL) with Batak culture to increase the interest of fourth grade students in learning fractions at SDN 067257, Medan Amplas District. The development model used is ADDIE which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The results of the study showed that the teaching materials developed had a very good level of validity, with the validity value increasing from 67% before the revision to 89% after the revision. The effectiveness of teaching materials in increasing students' interest in learning is relatively high, with a questionnaire score reaching 78%, which indicates that students are more interested and motivated in learning. In terms of practicality, the teacher's response to the use of teaching materials reached 92%, indicating that these teaching materials are very easy to use and in accordance with learning needs. Thus, these PBL-based teaching materials with Batak culture are worthy of being used as innovative and contextual learning media to increase students' interest in understanding fractions.